Exploring Personal Reading Histories in Developing Reading Interest of English Study Program Learners of University of Riau - Syofia Delfi; Fangiana Safitri Diah; Jismulatif Jismulatif (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
As one of activities in Extensive Reading classroom, Exploring Personal Reading Histories provides learners in exploring their reading experiences.   This study aimed to explore:  (1) What are the reading experiences of English study program learners of the Faculty of Teacher Training and Education University of Riau based in Exploring Personal Reading Histories?” (2) How are the reading experiences of English study program learners of the Faculty of Teacher Training and Education University of Riau based on Exploring Personal Reading Histories developing reading interest?”It was a case study and the data were collected through the document of learners ‘reading histories.  The result of this study found that:  (1) the reading experiences of English study program learners of the Faculty of Teacher Training and Education University of Riau based on Exploring Personal Reading Histories is individual contexts and processes in becoming competent for each level. (2) The reading experiences of English study program learners of the Faculty of Teacher Training and Education University of Riau based on Exploring Personal Reading Histories developing reading interest are through reading experiences developing processes (parent’s and teachers’ role, learners’ positive attitude, reading materials for each level, reading activities, building critical thinking). This study suggests implementing Exploring Personal Reading Histories in Extensive Reading course. It is also recommended conducting deep study on Exploring Personal Reading Histories in developing reading interest by using socio-cultural theory and interviews as additional theory and interview.